Rayleigh–Taylor instability in partially ionized prominence plasma. Issue Volume 8:Issue S300(2013) (6th January 2014) - Khomenko, E.; Díaz, A.; de Vicente, A.; Collados, M.; Luna, M.
Abstract: We study Rayleigh–Taylor instability (RTI) at the coronal–prominence boundary by means of 2.5D numerical simulations in a single-fluid MHD approach including a generalized Ohm's law. The initial configuration includes a homogeneous magnetic field forming an angle with the direction in which the plasma is perturbed. For each field inclination we compare two simulations, one for the pure MHD case, and one including the ambipolar diffusion in the Ohm's law, otherwise identical. We find that the configuration containing neutral atoms is always unstable. The growth rate of the small-scale modes in the non-linear regime is larger than in the purely MHD case.